Еволюція фінансового механізму пенсійного забезпечення - Чугунов, І. Я.; Насібова, Ольга Вікторівна (Державний торговельно-економічний університет, 2016)
Розкрито передумови виникнення фінансового механізму пенсійного забезпечення населення. Визначено особливості становлення системи фінансового регулювання пенсійного захисту громадян. Здійснено аналіз фінансування державних видатків на пенсійні виплати в середині ХІХ та на початку ХХ ст. Виявлено основні чинники впливу на рівень пенсійного забезпечення населення та розвиток основ функціонування фінансового механізму пенсійної системи.

In order to determine the economic substance of the operation of the pension system in terms of institutional reforms and directions of further development of relations of pension disclosure is appropriate characteristics of the financial mechanism of formation of the pension system. Improving the quality of public pension protection should be accompanied by effective changes in the financial policy of the country, improving the mechanisms of state control of social and economic development of society. The question of adequate pension provision as a significant social component needs to be addressed together with the use of financial instruments, based on macroeconomic and demographic trends. Currently, it is necessary to deepen the theoretical foundations of financial security pension system with relevant historical experience, which will provide an opportunity to strengthen the impact of financial regulation on social development in the country.
Evolution of the financial mechanism of pension protection
Keywords: пенсійне забезпечення; державні видатки; пенсійний захист громадян; фінансовий механізм; пенсійні виплати; фінансове регулювання; пенсійні каси страхового типу; pensions; government spending; pension protection of citizens; financial mechanism; pension payments; financial regulation; pension fund insurance type